Advancing Global Governance: : Integrating the Concept of a Shared Future for Humanity with International Environmental Rule of Law - de Castro, Douglas (Revista de Direito Internacional e Globalização Econômica, 2024)
The concept of a community with a shared future for humanity represents China’s vision for global governance in the new era of globalization, with a environmentally sustainable world as its central tenet. The international environmental rule of law is crucial for building a global ecological civilization. However, achieving this goal is hindered by significant challenges, including the fragmentation of international environmental law, weak implementation mechanisms, and insufficient frameworks for resolving environmental disputes. By leveraging its rich connotation, the concept of a shared future for humanity can be pivotal in advancing the international environmental rule of law. This includes strengthening the foundational principles of international environmental law, guiding the development of a more cohesive legal framework, enhancing enforcement mechanisms, and fostering international coordination in environmental dispute resolution. To that end, this study argues that the concept of a shared future for humanity is critical to incorporate alternative worldviews within the existing international order, reinforcing the international environmental rule of law. This involves translating the vision into the language of international environmental law and establishing innovative platforms to integrate the concept with legal and institutional approaches to global environmental governance.